Kedudukan Bukti Elektronik Untuk Membangun Keyakinnan Hakim Dalam Perkara Tindak Pidana Umum (Studi kasus perkara pembunuhan berencana atas Nama Jessica Kumala Wongso) - Kuo Bratakusuma; Alvi Syahrin; Sunarmi Sunarmi; Mahmud Mulyadi (Jurnal Pencerah Bangsa, 2024)
Judge in the decision of the Central Jakarta District Court No. 777/Pid.B/ 2016/PN.JKT.PST in conjunction with the Jakarta High Court Decision No. 393/PID/2016/PT.DKI jo the Supreme Court Decision No. 498 K/PID/2017 believes that the death of the victim of a crime is based on poison that enters his body through coffee. This is based on evidence presented in court, including CCTV. This research is a normative and descriptive analytical study that describes and analyzes a phenomenon related to the Position of Electronic Evidence to Build Judges' Conviction in General Crime Cases (Case Study of Planned Murder Cases on behalf of Jessica Kumala Wongso). The results of the study, the legal rules for electronic evidence in criminal procedural law in Indonesia are not contained or included in the Criminal Procedure Code, but are contained in several regulations that regulate specific crimes, namely: Article 5 of Law No. 11 of 2008, Article 41 of Law no. 36 of 1999, Article 26 A of Law no. 20 of 2001, Article 44 paragraph (2) of Law No. 30 of 2002, Article 27 of Law no. 15 of 2003, Article 29 of Law no. 21 of 2007, Article 24 of Law no. 44 of 2008, Article 96 letter f of Law no. 32 of 2009, Article 86 paragraph (2) of Law no. 35 of 2009, Article 73 letter b of Law No. 8 of 2010 and Article 38 of Law no. 9 of 2013